2004
DOI: 10.1105/tpc.018705
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the Petunia hybrida α-Expansin Gene PhEXP1 Reduces the Amount of Crystalline Cellulose in Cell Walls and Leads to Phenotypic Changes in Petal Limbs

Abstract: The expansins comprise a family of proteins that appear to be involved in the disruption of the noncovalent bonds between cellulose microfibrils and cross-linking glycans, thereby promoting wall creep. To understand better the expansion process in Petunia hybrida (petunia) flowers, we isolated a cDNA corresponding to the PhEXP1 a-expansin gene of P. hybrida. Evaluation of the tissue specificity and temporal expression pattern demonstrated that PhEXP1 is preferentially expressed in petal limbs during developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
129
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(145 citation statements)
references
References 69 publications
7
129
0
2
Order By: Relevance
“…Numerous proteins and enzymes are required for cell expansion. Genes encoding expansin, which is involved in cell wall loosening, are expressed during flower opening of carnation (Harada et al, 2011), Mirabilis jalapa (Gookin et al, 2003), and Petunia hybrida (Zenoni et al, 2004), and xyloglucan endotransglycosylase/ hydrolase (XTH) activity is associated with the opening of sandersonia flowers (O'Donoghue et al, 2002). Recently, Ochiai et al (2013a) reported that the expression of expansin and XTH genes and their proteins increased during flower opening in Eustoma.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous proteins and enzymes are required for cell expansion. Genes encoding expansin, which is involved in cell wall loosening, are expressed during flower opening of carnation (Harada et al, 2011), Mirabilis jalapa (Gookin et al, 2003), and Petunia hybrida (Zenoni et al, 2004), and xyloglucan endotransglycosylase/ hydrolase (XTH) activity is associated with the opening of sandersonia flowers (O'Donoghue et al, 2002). Recently, Ochiai et al (2013a) reported that the expression of expansin and XTH genes and their proteins increased during flower opening in Eustoma.…”
Section: Discussionmentioning
confidence: 99%
“…Some enzymes, such as invertase and sucrose synthase, are involved in the accumulation of soluble carbohydrates. Expansin, which is involved in cell wall loosening, is expressed during flower opening of tomato (Brummel et al, 1999), Mirabilis jalapa (Gookin et al, 2003) and Petunia hybrida (Zenoni et al, 2004), and xyloglucan endotranglycosylase/hydrolase (XTH) activity is associated with the opening of sandersonia flowers (O'Donoghue et al, 2002). We are now investigating enzyme activity and the gene expression responsible for cell expansion associated with flower opening.…”
Section: Discussionmentioning
confidence: 99%
“…6 The use of PCA in conjunction with FTIR spectroscopy has proved to be an important tool in the study of cell wall structure and composition heterogeneity in a species, 7,8 or among different species, 5,9-11 as well as in the identification and classification of mutants with altered cell wall compositions. 6,[12][13][14] This approach has been also very useful in the characterization of the modifications appearing in this kind of mutants [15][16][17][18][19][20] or in transgenic plants with altered cell walls 21 and in the modifications to cell wall composition induced by different biotic or abiotic stress factors.…”
Section: Why Study Cell Walls?mentioning
confidence: 99%